Antimicrobial and antibiofilm evaluation of thymol, sodium azide, and sodium lauryl sulfate against multidrug-resistant pathogens: An integrated experimental and computational study - Kamal A. Qureshi; Adil Parvez (PLoS ONE, 2026)
Multidrug-resistant (MDR) pathogens represent a major global health challenge, underscoring the urgent need for new antimicrobial strategies that can effectively target both planktonic cells and biofilm-associated infections. This study integrated in vitro antimicrobial and antibiofilm assays with comprehensive in silico analyses to evaluate the repurposing potential of thymol (TM), sodium azide (SA), and sodium lauryl sulfate (SLS) against 17 bacterial and two fungal strains, including methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates. TM showed the strongest overall antimicrobial activity, with low MIC/MBC values (0.10–0.20 mg/mL) and potent antibiofilm effects (MBIC: 0.20–0.39 mg/mL; MBEC: 0.39–0.78 mg/mL). In contrast, SA exhibited similar MICs (0.10–0.78 mg/mL) but required much higher concentrations for bactericidal and antibiofilm endpoints (MBC/MBIC/MBEC 6.25–100 mg/mL), whereas SLS displayed variable activity, with low MICs against most Gram-positive bacteria (0.10–0.20 mg/mL) but high MBC/MBIC/MBEC values (50–100 mg/mL), especially for Gram-negative biofilms. Molecular docking and 300 ns molecular dynamics (MD) simulations revealed that TM forms stable complexes with key microbial targets, most notably FtsZ ( ΔG = –11.0 kcal/mol; K d = 3.2 × 10 ⁻ ¹⁰ M), supported by favorable MM/GBSA binding energies and restrained motions in principal component analysis/free-energy landscape (PCA/FEL) analyses. SA and SLS were primarily used as mechanistic comparators (respiratory inhibitors and membrane disruptors, respectively). In contrast, their non-ionic analogs, phenyl azide (PA) and lauryl sulfate (LS), were explored as potential scaffolds. LS showed a very high predicted affinity for UDP-3-O-acyl- N -acetylglucosamine deacetylase (LpxC) ( ΔG = –19.9 kcal/mol; K d = 1.7 × 10 ⁻ ¹¹ M), indicating promise for future optimization. In silico ADMET profiling identified TM as the most balanced candidate, combining broad-spectrum antibiofilm efficacy with a comparatively favorable predicted safety profile. Overall, TM emerges as a viable repurposable antimicrobial agent, whereas LS-based derivatives represent computationally prioritized scaffolds that warrant further experimental validation.